Numerical simulation of thermal-hydraulic characteristics in a closed natural circulation system. Issue 2 (February 2019) - Wang, Qiang; Gao, Puzhen; Xu, Yuting; Zhang, Yinxing; Lin, Yuqi; Wang, Zhongyi
Abstract: In order to enhance the safety of nuclear energy, natural circulation served as a passive technology is widely used. Accordingly, an investigation associated with thermal-hydraulic characteristics for natural circulation system is made in this work. Numerical simulation based on RELAP5 code is performed especially for flow instability phenomenon. The results indicate that flashing and condensation are two important factors for low pressure natural circulation two-phase system. For all this, the tolerance of natural circulation to flashing oscillation could be enhanced effectively with the increase of system pressure. Under high pressure condition, the flowrate might shrink to a new equilibrium state from flashing-induced oscillation. The simulation results and analysis could contribute to a more extensive utility of natural circulation mechanism for nuclear energy.